Clinical picture, differential diagnosis and therapy of patients with lichen planus - L. A. Yusupovа; E. I. Yunusovа; Z. Sh. Garaeva; G. I. Mavlyutova; K. F. Khairetdinova; E. V. Bildyuk; D. I. Yapparova (Лечащий Врач, 2021)
The article presents data on the red flat lichen, chronic skin disease of mucous membranes, scalp, nail plates. Etiological and pathogenetic mechanisms leading to the development of lichen planus, the clinical picture and differential diagnosis of the disease are given, information about the methods of therapy and prevention is presented.